Performance Modelling for Mobile Cellular Network Using Queueing System - Basi, Hussein Muzahim Aziz (1999)
Mobile networking technology has been in existence for more than twenty years, but only in the past decade has it become commercially popular. With computers however increasingly portable and networks more accessible, users are coming demanding to the same network services from mobile network as they have been accustomed to obtaining from stationary wireline networks. Mobile communication can be defined as any communications network in which at least one of the constituent entities (users, switches, or a combination of both) change location, relative one to another. One of the most important problems in the design of a cellular system is deciding on the optimal configuration of it. The designers must evaluate the possible con figurations of the system components and their characteristics in order to develop a system with greater efficiency. The parameters useful to measure different parts performance of the system are: voice quality, frequency spectrum efficiency and grade of service (GOS). The grade of service (GOS) gives a form to measure a system's performance, and with it the proportion of non-served calls can be known. GOS in cellular systems is effected not only by the systems traffic but also by cochannel interference (outage). In this thesis, the analytical study of the grade of service (GOS) degradation in presence of outage for the mobile communication with queueing system is wanted. Two analytical models are proposed, the first model is with fixed outage rate, while the second model is the traffic dependent outage, where the outage is often dependent on the number of channels in use. Thus, the number of channels in outage can be considered as an indicator of the traffic load variations in the system. The performance parameters considered for the study from the above models are queue length, waiting time and probability of delay. The analytical results can show the benefit for considering the queueing in the cellular network, and can be used by designers in choosing appropriate design parameters to meet requirements.